Frequency of Salmonella Infection among Backyard and Commercial Duck Flocks in Iran, Serotyping and Drug Resistance Profile of Salmonella Isolated from Ducks - Javidnezhad, Javad; Peighambari, Seyed Mostafa; Razmyar, Jamshid; Barin , Abbas (Journal of Poultry Sciences and Avian Diseases, 2025)
Salmonella is one of the most important foodborne infections with worldwide distribution that infects humans and a wide range of animals. Poultry and poultry products are considered major sources of Salmonella infections for humans. Like chickens, ducks can play an important role in the transmission of Salmonella bacteria to humans. This study aimed to gain a deeper understanding of the frequency of Salmonella infection in ducks in Iran, as well as to determine the serovar and antimicrobial resistance patterns of Salmonella isolates. In this study, fecal samples were collected from four provinces of Iran. Each of the six fecal samples was pooled, resulting in a total of 352 samples. To isolate Salmonella, all samples were cultured using the standard techniques previously described. From a total of 352 stool samples, 20 Salmonella isolates (17.6%) were isolated and serotyped by using the slide agglutination test. Then, they were subjected to a polymerase chain reaction using Salmonella genus-specific primers and species-specific primers for serovars Enteritidis, Typhimurium, and Infantis. The disc diffusion method was used to determine the sensitivity of isolates to 21 antimicrobial agents. Serotyping identified 15 serovars of Enteritidis and three serovars of Typhimurium. Two isolates remained unknown. No isolate was resistant to ceftazidime, ceftriaxone, lincospectin, fosfomycin, and colistin. The resistance to other agents was variable. There were 17 resistance patterns to 21 antimicrobial agents. Among the resistant isolates, the occurrence of multiple resistance was very significant, as they showed resistance to at least one and up to 11 drugs. By comparing the findings of this study with those of other investigations in this field, it was shown that, like chicken flocks, Salmonella are circulating in duck flocks in Iran.